CONCEPTUAL APPROACHES TO FORMING AN INNOVATIVE MODEL FOR THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES UNDER SUSTAINABILITY CONDITIONS - SADOVNYK, Oleksandr; VOSTRIAKOV, Oleksandr; SKICHKO, Oleksiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines conceptual approaches to forming an innovative model for the development of agricultural enterprises under conditions of growing global transformations, digitalisation, and climate-related challenges. The relevance of transitioning Ukraine’s agricultural sector to a sustainable development model integrating economic efficiency, social responsibility, and environmental balance is substantiated. Key sectoral challenges are identified, including soil degradation, market volatility, resource constraints, increasing environmental requirements, and insufficient development of innovation infrastructure. An integrated scientific-practical model of innovative development is proposed, based on the combination of systemic, ecosystem, mechanism-based and model-based approaches. The content of the model’s technological, organisational, economic, social and environmental components is revealed, along with their contribution to strengthening long-term enterprise resilience. The organisational-economic mechanism ensuring alignment between sustainability goals, resource potential and managerial decisions is outlined. Special attention is paid to the role of digitalisation, human capital development, formation of an innovation-oriented culture, and strengthened cooperation between science, business and the state. The study also highlights the importance of aligning the development of Ukrainian agricultural enterprises with the European Green Deal and modern sustainability standards. The results confirm that implementing the proposed model enhances innovation activity, competitiveness and environmental resilience, creating favourable conditions for long-term balanced development of agricultural enterprises and contributing to national food security.